2010
DOI: 10.1590/s1413-81232010000400035
|View full text |Cite
|
Sign up to set email alerts
|

Perfil da condição bucal de idosas do Distrito Federal

Abstract: Perfil da condição bucal de idosas do Distrito FederalOral health status of elderly women from the Brazilian Federal District Resumo Os trabalhos realizados no Brasil a respeito das principais afecções bucais dos gerontes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
1
6
0
6
Order By: Relevance
“…Previous cross-sectional (17)(18)(19)(20) and demographic (21) studies with Brazilian elderly individuals have shown that edentulism varies from 61 to 87.1%. However, all of these studies indicate that tooth loss can not be considered as a natural process of aging, emphasizing the need to implement public health prevention and promotion policies (19,20) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous cross-sectional (17)(18)(19)(20) and demographic (21) studies with Brazilian elderly individuals have shown that edentulism varies from 61 to 87.1%. However, all of these studies indicate that tooth loss can not be considered as a natural process of aging, emphasizing the need to implement public health prevention and promotion policies (19,20) .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other studies corroborate the present sample. A research conducted in Distrito Federal (19) , (21) . With regard to the main orofacial characteristics, the majority of the sample presented a normal appearance/posture standard of the stomatognathic system's elements, in addition to scores closer to the normal according to AMIOFE-I protocol (9) .…”
Section: Discussionmentioning
confidence: 99%
“…It is stated that the ability to control the prosthesis contributes to changes in oral functions and interferes with speech production 33 ; thus, adaptation to the prosthesis is a factor to be considered in future studies, because the loss of teeth and poorly fitting dental prostheses create articulatory difficulties, worsened by decreased production of saliva and reduced orofacial muscle tone 15 . Research on vocal measures of elderly people who wear dental prosthesis are scarce and must be explored further, because the use of prostheses is common among the elderly 20,22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in countries like Brazil, most elderly people nowadays, especially those who had access to the public health system, have had essentially curative dental treatment, where the practice of tooth extraction was the main therapeutic procedure, which is why most elderly people wear prostheses on both dental arches, mainly in the upper arch 20,22,23 .…”
Section: Methodsmentioning
confidence: 99%
“…Há autores que afirmam que a doença periodontal, inclusive as bolsas periodontais, encontradas em grupos etários acima de 60 anos são, em sua maioria, mais severas VALSECKI JR, 2000;COSTA et al, 2010;FERREIRA et al, 2009 Frias et al (2011) realizaram um levantamento epidemiológico em uma população adulta na cidade de Guarulhos e concluíram que 9,1% da sua amostra apresentou sangramento gengival e em 53,6% foi observada a presença de cálculo.…”
Section: Iddunclassified